Assessment of skin flap viability using visible diffuse reflectance spectroscopy and auto-fluorescence spectroscopy - Liu, Quan (2013)
The accurate assessment of skin flap viability is vitally important in reconstructive surgery. Early identification of vascular compromise increases the change of successful flap salvage. The ability to determine tissue viability intraoperatively is also extremely useful when the reconstructive surgeon must decide how to inset the flap and whether any tissue must be discarded. Visible diffuse reflectance and auto-fluorescence spectroscopy, which yield different sets of biochemical information, have not been used in the characterization of skin flap viability simultaneously to our best knowledge. We performed both diffuse reflectance and fluorescence measurements on a reverse MacFarlane rat dorsal skin flap model to identify the additional value of auto-fluorescence spectroscopy to the assessment of flap viability. Our result suggests that auto-fluorescence spectroscopy appears to be more sensitive to early biochemical changes in a failed flap than diffuse reflectance spectroscopy, which could be a valuable complement to diffuse reflectance spectroscopy for the assessment of flap viability.